2018
DOI: 10.1002/app.47139
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation ofN,N‐diethyl‐meta‐toluamide (DEET) via miniemulsion polymerization for temperature controlled release

Abstract: N,N-diethyl-meta-toluamide (DEET), an insect repellent, can be successfully encapsulated in poly(n-butyl methacrylate-comethyl methacrylate) nanospheres via direct miniemulsion polymerization. Stable and low polydisperse nanospheres with a number average diameter of 114 AE 37 nm were obtained. It is shown that DEET is an effective costabilizer and that sodium lauryl sulfate is a suitable surfactant. The nanospheres glass-transition temperature (T g ) can be tuned by adjusting the ratio between n-butyl methacry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
(51 reference statements)
1
18
0
Order By: Relevance
“…The sustained release of nanoencapsulated DEET provided repellency for over 9 h, which was longer than obtained using free DEET. The results showed that the release mechanism was temperature dependent, which the authors highlighted as having great potential, since the release rate could be adjusted by alteration of temperature (Gomes et al, 2018). Silva et al (2019) encapsulated essential oils of Piper aduncum L. and Piper hispidinervum in gelatin nanoparticles and evaluated effect against Aedes aegypti Linn.…”
Section: Insect Repellentsmentioning
confidence: 99%
“…The sustained release of nanoencapsulated DEET provided repellency for over 9 h, which was longer than obtained using free DEET. The results showed that the release mechanism was temperature dependent, which the authors highlighted as having great potential, since the release rate could be adjusted by alteration of temperature (Gomes et al, 2018). Silva et al (2019) encapsulated essential oils of Piper aduncum L. and Piper hispidinervum in gelatin nanoparticles and evaluated effect against Aedes aegypti Linn.…”
Section: Insect Repellentsmentioning
confidence: 99%
“…For example, microcapsules composed of picaridin encapsulated with commercial antibacterial and antifungal microbiocide polymer demonstrated significant stability in water and maintained efficacious levels of insect repellency when adsorbed onto nylon‐cotton blended fabric 12 . Nanospheres containing DEET fabricated from miniemulsion polymerization resulted in sustained and temperature‐dependent release kinetics 13 . Furthermore, covalent attachment of DEET to nylon 6 via dye modification demonstrated some insect repellent activity, though chemical modification of DEET reduced efficacy in some cases 14 .…”
Section: Introductionmentioning
confidence: 99%
“…12 Nanospheres containing DEET fabricated from miniemulsion polymerization resulted in sustained and temperature-dependent release kinetics. 13 Furthermore, covalent attachment of DEET to nylon 6 via dye modification demonstrated some insect repellent activity, though chemical modification of DEET reduced efficacy in some cases. 14 While each of these approaches were effective, a material (ie, fiber) with insect repellent incorporated directly into it at the manufacturing stage would reduce the complexity of many of the coating and particle impregnation methods.…”
mentioning
confidence: 99%
“…Thus, the present work aims the encapsulation of ZnO and quercetin in polymeric nanoparticles, by miniemulsion polymerization technique, using octocrylene and green coffee oil as co-stabilizers to obtain high antioxidant activity and SPF, for application in sunscreen formulations. In addition, this work proposed the use of a copolymer with lower glass transition temperature [27] as encapsulating agent, aiming a better spreadability and retention of latex for application on the skin.…”
Section: Introductionmentioning
confidence: 99%